Pendidikan Jasmani Perspektif Filsafat Pendidikan Islam: Sistematic Literature Review - Hidayat, Azmar; Salminawati, Salminawati; Usiono, Usiono (Sekolah Tinggi Agam Islam Sumatera Medan, 2023)
Islamic education focuses more on the spiritual aspect, whereas the physical aspect is also important. While the body is one of the most important elements that make up humans. The body is a very important and influential aspect of the human being. Therefore, keeping and maintaining the body is important. This study aims to determine the form and concept of physical education in the perspective of Islamic education philosophy. The method in this research uses the Systematic Literature Review (SLR) approach. This approach aims to collect, review, and interpret all available evidence and information about physical education in the perspective of Islamic education philosophy. The results showed that physical education is very important and needs to be considered to maintain and care for the body and as a means of preparing a healthier and stronger generation. Through maintaining cleanliness, treating diseases, getting used to exercise and regulating eating and drinking patterns in everyday life. So that with physical education can help and facilitate the body to worship the almighty Allah. This research is certainly expected to be one of the references in people's lives about the importance of physical education.